Diagnosis and treatment of a rare sinonasal neuroendocrine tumour: adding to the evidence. (13th September 2016) - Gudlavalleti, Aashrai; Dean, Ryan; Liu, Yuxin; Dhamoon, Amit S
Abstract : Sinonasal neuroendocrine tumours (NETs) are rare, aggressive neoplasms with a high recurrence potential. There are no robust protocols for the management of these tumours. An 81-year-old man presented with an incidental sinonasal mass visualised on CT scan of head. Over the next few weeks he developed new onset, progressively worsening headache, right eye ptosis and restricted extraocular movements. Imaging confirmed a rapidly enlarging tumour involving the right nasal cavity and the orbit. Biopsy showed a large cell neuroendocrine carcinoma of the right ethmoidal sinus. The patient was treated with concurrent cisplatin chemotherapy and radiation. Repeat imaging showed decrease in tumour volume. The patient continues to do well and follows up regularly with our oncology service. Current protocols comprising chemotherapy after radiation are based on limited studies. A regimen involving concurrent chemoradiation also appears to aid in tumour volume reduction. Additional studies are required to formulate robust clinical protocols for management of sinonasal NETs.